Opening the Floodgates: The Implications of Increasing Platform Openness in Crowdfunding. (December 2017) - Wessel, Michael; Thies, Ferdinand; Benlian, Alexander
Managing platform ecosystems requires providers to govern the permeability of platform boundaries in order to strike a balance between openness and control. But is it worthwhile for platform providers to conduct screening processes for third-party offerings, or should they rather apply a laissez-faire approach and let the market determine winners and losers? In this study, we compare the market conditions on Kickstarter, one of the world's largest crowdfunding platforms, before and after a policy change that relaxed the previously stringent screening process for new campaigns. By analyzing over 230, 000 crowdfunding campaigns with a combined funding of over $1.9 billion that cover a 4-year period around the policy change, we find that increasing platform openness was a double-edged sword for the platform's ecosystem. While Kickstarter's revenue from commissions surged after the policy change due to an increase in the number of campaigns available on the platform, funding conditions for project creators and backers deteriorated. Project creators have to cope with lower success rates and an intensified competition due to a growing disproportion of backers to campaigns, while backers face higher uncertainties as project creators invest less in reducing information asymmetries. Our evidence from this natural experiment therefore suggests that increasing platform openness for third-party offerings can destabilize a platform's ecosystem. We thus extend the literature on platform openness and on the implications of policy changes on platform ecosystems. Our findings also provide practical insights for different platform stakeholders into possible "ripple effects" that are triggered when policy changes alter platform openness.